Prevalence of Obesity and its Co-Morbidities: A Study Among Thattankuttai Population of Namakkal District, India - Prasad, Amrita; Shylajakumari, Nisha Rani Sudhakaran; Kandasamy, Krishnaveni; Nallasamy, Venkateswaramurthy; Rajagopal, Shanmuga Sundaram; Ramanathan, Sambath Kumar (Indian Journal of Pharmacy Practice)
Background: In the past few decades the issue of overweight and obesity has become a serious public health concern throughout the world. In India, 5% of the population is obese. Obesity is not an immediately fatal disease by itself, but is a risk factor for wide range of serious non communicable diseases in Indian population. Aims: This study was aimed to investigate the prevalence of obesity in a rural village, Thattankuttai population at Namakkal district, Tamil Nadu, India and to evaluate its relationship with hypertension, anemia and diabetes. Materials and Methods: This cross sectional study comprised of 215 subjects attending a local medical camp, aged between 18 – 80 yrs. Heights, weight, body mass index, systolic and diastolic blood pressure, random blood sugar, hemoglobin levels were monitored using standard methods. Results: Prevalence of overweight and obesity was 14.4% and 60.46% respectively and it was predominant among women (62%) than men (59.7%). Systolic blood pressure, diastolic blood pressure and random blood sugar were significantly elevated in obese subjects than in normal BMI subjects (control). Anemia was more prevalent among underweight (100%) and normal weight (81.61%) than in obese patients (59.53%). Conclusion: The results showed a higher trend of hypertension and diabetes and decreased trend of anemia with increase in body mass index. Periodic health camps, conducted at different places throughout India may help to detect diabetes, hypertension and anemia in undiagnosed population and thereby preventing the disease progression and complications.
Keywords: Overweight; Obesity; Hypertension; Diabetes; Anemia